Engineering in Oxygen-incorporated monolayer MoS2 for Effi-cient Hydrogen Evolution - Jianling MENG; Zheng WEI; Shuhua YANG; Xiao REN (Medžiagotyra, 2024)
MoS2 is a promising alternative to Pt in hydrogen evolution reaction (HER) due to its low cost. To enhance the catalytic properties of the 2H MoS2 inert basal plane, we propose an approach of employing oxygen incorporated MoS2 as a catalyst for HER. Different density of oxygen substitution doped monolayer MoS2 samples (MoS1.51O0.49, MoS1.55O0.45, MoS1.67O0.33) were achieved by chemical vapor deposition method and their catalytic performance were tested. Experimentally, we demonstrate that oxygen substitution can activate the inert basal plane and the catalytic performance is dependent on the oxygen substitution percentage. Also, combining with DFT calculations, we confirm that oxygen substitution act as catalytic sites. Our work provides a strategy for enhancing of monolayer MoS2 HER activities through in situ substitution doping.